Community demands and resources and work-family conflict : An exploratary study - Zaiton, Hassan; Nor Afiza, Hasnan (Universiti Malaysia Sarawak, UNIMAS, 2014)
Most studies on work-life balance examine only work and family domain. While work is the only role in its domain, life consists of many roles besides family. However, research on other roles is still very limited. The study is to examine the influence of community (neighbor, neighborhood, relatives, friends and participation in NGO) demands and resources on work-family conflict (WFC) and family-work conflict (FWC). Questionnaires were distributed to 506 employees from six public and private organizations in Kuching, Sarawak. Data was analyzed using the Statistical Package of The Social Science (SPSS) version 19 for the Pearson Correlations and Structural Equation Modeling (SEM) using AMOS Version 20. The findings showed that WFC was negatively related with demands from neighbors, relatives and friends; and positively related with demands from participating in NGO and resources from neighbors. FWC was negatively related with demands from neighbors, relatives and friends, and positively related with resources from neighbors and relatives. The study provides evidence that community domain influence the WFC and FWC. Thus, organizations should consider community domain in formulating strategies to minimize WFC and FWC experienced by the employees.